Democracy before the court: Democracy as a justiciable concept in the Eu - Conway Gerard (Filozofija i Društvo, 2025)
Democracy is a justiciable concept under EU law. Beyond identifying the EU as being a representative democracy, the EU treaties provide relatively little guidance of what democracy entails. The context is the contestedness of the concept of democracy, especially across 27 polities of the Member States of the EU, and the potentially extensive review of national constitutional orders that could result from the jurisdiction of the Court of Justice of the EU regarding Article 2 TEU (Treaty on European Union) as a statement of foundational values of the EU. This paper considers, in particular, how the concept of democracy interacts with the other values in Article 2, principally, the rule of law and respect for human rights. The jurisdiction of the Court of Justice under Article 2 highlights the problem of determining the relative importance and interaction of the fundamental values of the EU given their relative incommensurability, including the problems of i. relating democracy at national and supranational levels in the EU and of ii. the limits of democratic authority. It is argued that Article 2 should be understood as presenting a complex problem of the inter-relationship of values for which a method of reflective equilibrium and a threshold test are essential for their application as justiciable concepts. Applying this framework or approach, the final part considers some examples of national practices relating to democracy that could be considered contrary to the values of democracy in EU law and subject to jurisdiction under Articles 2 and 7 TEU: the lengthening of parliamentary terms, recall procedures, and militant democracy.